Vertical stratification of fatty acids in the blubber of southern elephant seals (Mirounga leonina): implications for diet analysis - Best, NJ; Bradshaw, CJA; Mark Hindell; Nichols, PD (2003)
Fatty acid signature analysis (FASA) is a powerful ecological tool that uses essential fatty acids (FA) from the tissues of animals to indicate aspects of diet. However, the presence of vertical stratification in FA distribution throughout blubber complicates the application of FASA to marine mammals. Blubber biopsy samples were collected from adult female southern elephant seals (Mirounga leonina) from Macquarie Island (n=11), and blubber cores were divided into inner and outer sections to determine the degree to which the blubber layer was stratified in FA composition, we found 19 FA from both blubber layers in greater than trace amounts (>0.5%). The inner and outer blubber layers could be separated using principal components analysis based on the relative proportion of FA in each layer. Dietary polyunsaturated fatty acids (PUFA) were also observed in significantly higher proportions in the inner blubber layer. Due to the degree of FA stratification in southern elephant seals, we concur with other marine mammal studies that sampling only the outer blubber layer will result in a loss of recently accumulated information regarding diet structure (as indicated by 'surplus' PUFA from the diet). This finding suggests that differential mobilization/deposition of certain FA may result in a modified signature from prey to predator. Thus, sampling animals to recover the inner blubber layer is important for studies attempting to describe aspects of marine mammal diet. This can be achieved in animals such as pinnipeds where the whole blubber layer can be readily sampled. Â© 2002 Elsevier Science Inc. All rights reserved.